Blood Sugar, Your Pancreas, and Unicorns: The Development of Health Education Materials for Youth With Prediabetes. Issue 4 (July 2019) - Yazel-Smith, Lisa G.; Pike, Julie; Lynch, Dustin; Moore, Courtney; Haberlin, Kathryn; Taylor, Jennifer; Hannon, Tamara S.
Background. The obesity epidemic has led to an increase in prediabetes in youth, causing a serious public health concern. Education on diabetes risk and initiation of lifestyle change are the primary treatment modalities. There are few existing age-appropriate health education tools to address diabetes prevention for high-risk youth. Aim . To develop an age-appropriate health education tool(s) to help youth better understand type 2 diabetes risk factors and the reversibility of risk. Method . Health education tool development took place in five phases: exploration, design, analysis, refinement, and process evaluation. Results . The project resulted in (1) booklet designed to increase knowledge of risk, (2) meme generator that mirrors the booklet graphics and allows youth to create their own meme based on their pancreas' current mood, (3) environmental posters for clinic, and (4) brief self-assessment that acts as a conversation starter for the health educators. Conclusion . Patients reported high likability and satisfaction with the health education tools, with the majority of patients giving the materials an "A" rating. The process evaluation indicated a high level of fidelity and related measures regarding how the health education tools were intended to be used and how they were actually used in the clinic setting.